In vitro anti-HSV-1 activity of a chemically sulfated galactomannan from Leucaena leucocephala seeds - E. Gemin; C.E.O. Ferreira; M.R. Sierakowski; T.R. Jorge; M.E.G. Joineau; L. Ono (São Paulo State University (UNESP), 2010)
A galactomannan extracted from the seeds of Leucaena leucocephala was sulfated chemically, yielding a polymer (LLS-2) with 15.2% sulfate by weight (degree of sulfation 0.60), and its effect on the replication of Herpes simplex virus 1 (HSV-1) in Vero cells was investigated. When added during infection and early replication, LLS-2 showed 93.7% inhibition of HSV-1 replication at a concentration of 2.5 μg/mL, according to the reduction in the number of viral plaques, and a selectivity index higher than 1,000, suggesting that it inhibits HSV-1 binding to the host cell.